Determination of Habits of Mind and their Relationship with Creativity among Students of Excellent Academic Achievement at Qatar University during the COVID-19 Crisis - Fakhrou, Abdulnaser A.; Ghareeb, Sara A. (Modern Perspectives in Language, Literature and Education Vol. 7, 2021)
During the COVID-19 crisis, the current study aims to investigate the relationship between the amount of possessing habits of mind and creativity among students of great academic accomplishment at Qatar University. A descriptive analytical method was used by the researchers. The researchers chose a sample of 12 male students and 250 female students who had excelled in their studies. They were enrolled at the College of Education at Qatar University. They were selected through using the random stratified sampling method was used. Questionnaire forms were distributed to those students through using e-mail. However, 5 questionnaire forms were excluded due to having missing data and 7 questionnaire forms weren’t retrieved. Thus, the final sample consists from 250 female students. SPSS program was used to analyze data. It was found that extent of having habits of mind by students of excellent academic achievement at Qatar University is moderate. It was found that the creativity level of the students of excellent academic achievement at Qatar University is moderate. It was found that there is a statistically significant positive relationship between that extent of having habits of mind and creativity level at Qatar University during the COVID-19 crisis. The researchers recommend adding activities that requires using habits of mind to university curricula in Qatar.